2019
DOI: 10.1002/biot.201900349
|View full text |Cite
|
Sign up to set email alerts
|

Three‐Enzyme Phosphorylase Cascade for Integrated Production of Short‐Chain Cellodextrins

Abstract: Cellodextrins are linear β‐1,4‐gluco‐oligosaccharides that are soluble in water up to a degree of polymerization (DP) of ≈6. Soluble cellodextrins have promising applications as nutritional ingredients. A DP‐controlled, bottom‐up synthesis from expedient substrates is desired for their bulk production. Here, a three‐enzyme glycoside phosphorylase cascade is developed for the conversion of sucrose and glucose into short‐chain (soluble) cellodextrins (DP range 3–6). The cascade reaction involves iterative β‐1,4‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 67 publications
(110 reference statements)
2
42
0
Order By: Relevance
“…Besides the considerations of overall immobilization efficiency of each individual enzyme (Figure 2), we took into account that the DP-controlled synthesis of celloÀ oligosaccharides necessitates the three phosphorylases to be present in a balanced ratio of activities. In previous studies of the cascade reaction in solution, [30] we identified a favorable ratio 10 : 2 : 3 for the activities of ScP, CbP and CdP. The activity of the immobilized enzymes was 234 U/g (ZÀ BlScP), 49 U/g (ZÀ CuCbP) and 74 U/g (ZÀ CcCdP), thus well in line with the required ratio of activities for efficient production.…”
Section: Three-enzyme Co-immobilization For Celloà Oligosaccharide Prsupporting
confidence: 74%
See 4 more Smart Citations
“…Besides the considerations of overall immobilization efficiency of each individual enzyme (Figure 2), we took into account that the DP-controlled synthesis of celloÀ oligosaccharides necessitates the three phosphorylases to be present in a balanced ratio of activities. In previous studies of the cascade reaction in solution, [30] we identified a favorable ratio 10 : 2 : 3 for the activities of ScP, CbP and CdP. The activity of the immobilized enzymes was 234 U/g (ZÀ BlScP), 49 U/g (ZÀ CuCbP) and 74 U/g (ZÀ CcCdP), thus well in line with the required ratio of activities for efficient production.…”
Section: Three-enzyme Co-immobilization For Celloà Oligosaccharide Prsupporting
confidence: 74%
“…We used the conditions previously established for the enzymatic cascade reaction in solution: 200 mM sucrose, 65 mM glucose and 50 mM phosphate. [30] The volumetric activity of the immobilized enzymes in suspension was 9 U/mL for ZÀ BlScP, 2 U/mL for ZÀ CuCbP and 3 U/mL for ZÀ CcCdP. As shown in Figure 5B,~90 % of the initial sucrose was converted within 3 hrs and celloÀ oligosaccharides were released concomitantly.…”
Section: Three-enzyme Co-immobilization For Celloà Oligosaccharide Prmentioning
confidence: 91%
See 3 more Smart Citations